"When We Learn Better, We Do Better": Describing Changes in Empowerment Through Photovoice Among Community Health Advisors in a Breast and Cervical Cancer Health Promotion Program in Mississippi and Alabama. (May 2014) - Mayfield-Johnson, Susan; Rachal, John R.; Butler, James
As change agents in the community, community health advisors (CHAs) are a viable solution to bridge the gap between health service delivery systems and the community. With many CHAs members of the underserved and minority populations they serve, change and empowerment experienced by CHAs should be documented. This phenomenological study describes the empowerment change processes of 30 African American CHAs who participated in focus groups that used photovoice, and were part of a breast and cervical cancer health promotion program in Mississippi and Alabama. Using photos and narratives as primary research methods, these CHAs gave voice to an often-overlooked resource in the improvement of vulnerable populations in the education and promotion of the community's health.